Efficacy of preoperative trimetazidine for preventing myocardial injury in patients undergoing off-pump coronary artery bypass grafting - Turk, Tamer; Ata, Yusuf; Aydin, Ufuk; Ari, Hasan; As, Kagan Ahmet; Yavuz, Senol (The European Research Journal, 2016)
Objective. Off-pump coronary artery bypass grafting (CABG) with median sternotomy have been shown to be beneficial and associated with reduced myocardial injury. However, there is still a risk for ischemic myocardial injury that results from the normothermic and metabolically active myocardium during the occlusion of the target coronary artery. We aimed to evaluate the efficacy of trimetazidine in prevention of myocardial tissue injury in patients undergoing off-pump CABG by measuring serum levels of cardiac troponin I (cTnI). Methods. Thirty patients undergoing first-time elective off-pump CABG were randomly assigned to two groups: 15 patients received trimetazidine 60 mg orally per day (trimetazidine group) for three weeks and 15 patients received placebo (control group). As a parameter of myocardial injury, we measured cTnI levels. Blood samples were taken sequentially from the patients before surgery (t1), 30 minutes after the last distal anastomosis (t2), at postoperative 12th hour (t3) and at postoperative 24th hour (t4). cTnI measurements were made by direct chemiluminometric technology. Results. Baseline and operative characteristics of patients are similar. All preoperative serum cTnI concentrations were within the normal range and rose with the beginning of the operation which reached to its peak value at t3 in the control group and t4 in trimetazidine group. When the increase in the serum cTnI concentrations of trimetazidine group and control group were compared there was a slight numerical increase in cTnI levels in all measurements after reperfusion but reached to statistical significance only at t3 (mean: 0.40 ng/ml; mean rank: 12.20; range: 0.05-1.66 vs. mean: 0.20 ng/ml; mean rank: 18.80; range: 0.11-0.30; p=0.041). Conclusion. Preoperative treatment with trimetazidine might reduce postoperative myocardial injury in patients undergoing first time isolated off-pump CABG, but larger randomized placebo controlled trials are still for recommendation of routine pretreatment with trimetazidine.